Breast Cancer Knowledge and Screening Practice among Women in Makkah, Saudi Arabia - Flemban, Arwa F; Kabrah, Saeed M; Alfaifi, Suhail S; Alsubhi, Ahmed S; Alzahrani, Ayoub S; Alhazmi, Khalid A; Alharbi, Samah (Journal of Contemporary Medical Sciences, 2022)
Objectives: This study aimed to estimate the level of current knowledge regarding breast cancer in Saudi Arabia. We assessed the knowledge of breast cancer risks, the knowledge regarding the BSE and mammogram in Saudi Arabian females using a survey-based study. Methods: A cross-sectional study was conducted using a self-administered survey to assess the knowledge and practice of Saudi women toward Brest cancer examination. Collected data were analyzed using SPSS program. Results: A total number of 499 surveys were collected. The data showed that there was general lack of practice of BSE in the sample only 186 (37%) reported that they practiced regular BSE and only 16 (3%) reported that they went to the clinic for breast examination. Among all participants around 54% had poor overall knowledge of breast cancer 65% had poor knowledge regarding breast cancer risk and 93% had poor knowledge regarding clinical examination. Surprisingly, 56% had good knowledge regarding the clinical picture of breast cancer. Conclusion: This clearly showed that the lack of breast self-examination, mammogram and clinical examination is not a result of total lack of knowledge but due to lack of knowledge regarding risks and examination. This set of data provide a guideline for the focus and planning of future breast cancer awareness campaigns.